Fractional integro-differential equations with nonlocal conditions and ψ–Hilfer fractional derivative - Abdo, Mohammed S.; Panchal, Satish K.; Shafei Hussien, Hussien (Mathematical Modelling and Analysis, 2019)
Considering a fractional integro-differential equation with nonlocal conditions involving a general form of Hilfer fractional derivative with respect to another function. We show that weighted Cauchy-type problem is equivalent to a Volterra integral equation, we also prove the existence, uniqueness of solutions and Ulam-Hyers stability of this problem by employing a variety of tools of fractional calculus including Banach fixed point theorem and Krasnoselskii's fixed point theorem. An example is provided to illustrate our main results.